Complete mitochondrial genome of the ring-necked pheasant, Phasianus colchicus (Galliformes: Phasianidae). (April 2013) - Li, Xifeng; Ren, Qiongqiong; Kan, Xianzhao; Qian, Chaoju; Li, Xixi; Qian, Min
<x xml:space="preserve">Abstract</x> The complete mitochondrial genome of Phasianus colchicus is 16, 692 bp in length and composed of 13 typical protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and 1 putative control region. One extra nucleotide "C" is present in nad3 of P. colchicus, which is found in many other birds and is thought not to be translated. All protein-coding, rRNA, and tRNA genes have more than 99.0% nucleotide sequence similarity with the previously reported individual, except for cox3 and tRNAPro genes which has more similarity with Phasianus versicolor.